Product Defect Analysis in Bottled Water Manufacturing Using Six Sigma: Analisis Cacat Produk dalam Industri Pembuatan Air Kemasan Menggunakan Six Sigma - Nurdin, Muhammad Jabal Thoriq; Sulistiyowati, Wiwik (Indonesian Journal of Innovation Studies, 2025)
General Background Product quality control is a critical factor in manufacturing systems to ensure consistency and customer satisfaction. Specific Background Bottled drinking water production often experiences defects that reduce product quality and increase waste levels. Knowledge Gap Previous studies have applied quality control methods separately, with limited integration of Six Sigma, Fishbone Diagram, and Failure Mode and Effects Analysis (FMEA) for comprehensive defect analysis. Aims This study aims to identify dominant product defects, analyze root causes, and determine priority corrective actions in bottled water manufacturing. Results The findings indicate that several defect types dominate the production process, with low sigma level performance indicating the need for process improvement. Root causes are identified through fishbone analysis, while FMEA highlights the highest Risk Priority Number (RPN) as the main focus for corrective action. Novelty This study integrates multiple quality control tools to provide a structured and systematic evaluation of production defects. Implications The results support decision-making in improving production processes and reducing defect rates in manufacturing systems. Keywords: Quality Control, Product Defects, Six Sigma, FMEA, Manufacturing Key Findings Highlights Defect categories identified as dominant production issues Risk ranking prioritizes critical failure sources Integrated methods provide structured evaluation approach